2014
DOI: 10.2967/jnumed.114.141127
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Increased 64Cu Uptake by Human Copper Transporter 1 Gene Overexpression Using PET with 64CuCl2 in Human Breast Cancer Xenograft Model

Abstract: Copper is an essential cofactor for a variety of biochemical processes including oxidative phosphorylation, cellular antioxidant activity, and elimination of free radicals. The copper transporter 1 is known to be involved in cellular uptake of copper ions. In this study, we evaluated the utility of human copper transporter 1 (hCTR1) gene as a new reporter gene for 64 Cu PET imaging. Methods: Human breast cancer cells (MDA-MB-231) were infected with a lentiviral vector constitutively expressing the hCTR1 gene u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…64 Cu, with a half-life of 12.7 h, is the most widely studied PET radioisotope. It can be produced via the 64 Ni(p,n) 64 Cu reaction using a cyclotron in a carrier-free state (17). The optimal structure of the antibody-chelator conjugate for 64 Cu could be used for therapeutic b-emitter 67 Cu (half-life, 2.58 d) as a pair of radioisotopes of 64 Cu (18).…”
mentioning
confidence: 99%
“…64 Cu, with a half-life of 12.7 h, is the most widely studied PET radioisotope. It can be produced via the 64 Ni(p,n) 64 Cu reaction using a cyclotron in a carrier-free state (17). The optimal structure of the antibody-chelator conjugate for 64 Cu could be used for therapeutic b-emitter 67 Cu (half-life, 2.58 d) as a pair of radioisotopes of 64 Cu (18).…”
mentioning
confidence: 99%
“…Shortening the length of the aptamer for future labeling and imaging application may be essential. It has been recently shown that free 64 Cu accumulates in xenograft tumors (25). We addressed this issue by labeling the aptamer with 64 Cu and validating that there is no free copper in the blood and urine.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 , 16 , 17 Studies of yeast cells were the first to identify the specific genes that encode the proteins responsible for Cu uptake. For example, two proteins that exhibit a high affinity for Cu uptake, Ctr1 and Ctr3, were originally characterized in Saccharomyces cerevisiae , 14 , 16 , 17 while Ctr4 and Ctr5 were found to form heteromeric complexes in Schizosaccharomyces pombe. 17 Subsequently, homology searches of databases and complementation studies of yeast mutants identified both mouse and human CTR1 homologs.…”
mentioning
confidence: 99%
“… 17 Subsequently, homology searches of databases and complementation studies of yeast mutants identified both mouse and human CTR1 homologs. 16 In mammals, cellular import of Cu is primarily mediated via Ctr1 and Ctr2, and Ctr1 is the predominant transporter of dietary Cu from the intestinal lumen. 12 Details regarding the mechanisms responsible for mediating Cu uptake by human cells were limited until various Cu-binding proteins, referred to as Cu chaperone proteins, were identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation